Exploring the Nexus Between English Language Competency in Listening Skills and Emotional Social Development - Simanjuntak, Marudut Bernadtua (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This research embarks on a profound exploration into the intricate interplay between English language proficiency, with a specific emphasis on listening skills, and the emotional social development of young children within the realm of early childhood education. Employing a blend of descriptive qualitative research and an extensive literature review, this study unveils the profound impact of language competence on the emotional expression and social interactions of early learners. The findings unearth a spectrum of language proficiency levels among early childhood education students, influenced by factors such as extracurricular exposure to English and pedagogical approaches. Remarkably, students endowed with higher listening skill competence manifest increased self-assuredness in emotional expression and active participation in social interactions. Conversely, those with more restricted linguistic abilities encounter hurdles in articulating emotions and navigating social integration. The pivotal role of educators emerges as a central theme, where positive teacher-student relationships and inclusive classroom environments foster language development and emotional maturation. Moreover, this study delineates best practices and strategies, including interactive learning activities and family engagement, as potent tools for augmenting language proficiency within early childhood education settings. These profound insights accentuate the salience of linguistic development as an indomitable cornerstone of holistic child advancement and bear far-reaching implications for educators, policymakers, parents, and scholars alike, all with a shared aspiration of nurturing linguistic and emotional sagacity among the burgeoning minds of young learners